KAJIAN DESKRIPSI ANXIETY PADA IBU HAMIL PREOPERATIF SECTIO CAECAREA DI RUMAH SAKIT IBU DAN ANAK KABUPATEN MAGETAN - Nisa Ardhia; Sundari, Sundari; Frameswari, Fara (Fakultas Ilmu Kesehatan, 2024)
According to the World Health Organization (WHO), the increase in the implementation of Caesarean sections continues to increase at the global level. Based on data from the 2021 Indonesian Demographic and Health Survey, the incidence of Sectio Caesarea in Indonesia reached 17% of the total number of births. Sectio Caesarea is a surgical procedure that is commonly performed to help deliver a fetus because there are indications that it could threaten the health of the mother and fetus if delivered vaginally. The aim of this study was to examine the description of pregnant women's anxiety in facing surgical delivery. This research was conducted using a descriptive method using interview techniques with 20 respondents at RSIA Melati, Magetan Regency in January 2024. In the research process, several characteristics of pregnant women were found that influenced anxiety, namely age, parity, education and experience. Respondents' medical indications for having an SC were PEB, history of SC, breech position, CPD, history of asthma, post term, umbilical cord entanglement, placenta previa and transverse location. Respondents have various ways of dealing with anxiety, starting from searching for information on electronic media, sharing with people closest to them, to taking pregnancy yoga classes. The conclusion of this study is that primigravida respondents are more likely to feel anxiety than multigravidas because of their first experience facing childbirth.